Penerapan Intervensi Self-Management untuk Meningkatkan Perilaku on-Task pada Anak Usia Sekolah dengan Attention Deficit Hyperactivity Disorder (ADHD) Inattentive Type - Kanti Sekarputri Pernama; Erniza Miranda Madjid (Universitas Kristen Maranatha, 2019)
Children with attention-deficit/hyperactivity disorder (ADHD) often exhibit problem behavior and struggle in the classroom both academically and behaviorally. To be successful in school, children are required to have the ability to engage in tasks during learning activities (on-task behavior). One of the intervention known as an effective strategy to increase on-task behavior of school-age children diagnosed with ADHD is a behaviorally-based self-management technique. This study was designed for a fifth grade student aged 11 years old with ADHD predominantly inattentive type. The study took place in an inclusive school at Bojong Gede. Using a single case AB design, four self-management strategy were implemented to increase the on-task behavior. Each baseline and follow-up data was collected over four days, while the intervention it self was implemented over 16 days. The result indicated that the self-management technique appeared to be effective in increasing on-task behavior of participant (from 38% to 90,5%). Keywords: ADHD, on-task; academic engagement, self-management; student